2016
DOI: 10.1177/1078087416663004
|View full text |Cite
|
Sign up to set email alerts
|

“Outsiders with Deep Pockets”: The Nationalization of Local School Board Elections

Abstract: Recent election cycles have seen growing attention to the role of “outside” money in urban school board elections. Using an original data set of more than 16,000 contributions covering election cycles from 2008 to 2013 in four school districts (Los Angeles, CA; New Orleans, LA; Denver, CO; Bridgeport, CT), we show how large national donors play a significant role. Our study links two dynamic fields that are rarely studied together: (1) the behavior of wealthy donors in a changing national campaign finance syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…Another contributing factor has been the development and influence of a procharter/school choice national network of interest groups, foundations, nonprofit organizations, and business leaders (Reckhow, 2010(Reckhow, , 2013Reckhow et al, 2017). These organizations and individuals have provided advocacy support, expertise, and funding in districts that have moved in the PMM direction, including financial contributions to support the election of prochoice/PMM school board candidates (Reckhow et al, 2017;Welsh & Hall, 2018).…”
Section: Empirical Literaturementioning
confidence: 99%
“…Another contributing factor has been the development and influence of a procharter/school choice national network of interest groups, foundations, nonprofit organizations, and business leaders (Reckhow, 2010(Reckhow, , 2013Reckhow et al, 2017). These organizations and individuals have provided advocacy support, expertise, and funding in districts that have moved in the PMM direction, including financial contributions to support the election of prochoice/PMM school board candidates (Reckhow et al, 2017;Welsh & Hall, 2018).…”
Section: Empirical Literaturementioning
confidence: 99%
“…Over the past several years, there has been increased attention in the politics of education to the role of philanthropies in the politics of urban board elections (Reckhow et al 2017;Henig, Jacobsen, and Reckhow 2019). There has similarly been attention to the role that intermediary organisations play in disseminating research and information to policymakers about 'incentivist' educational policies such as charter schools in urban contexts (Scott and Holme 2016), as well as new studies of how national philanthropies are funding charter management organisations, or CMOs (Ferrare and Setari 2018;Quinn, Oelberger, and Meyerson 2016;Scott 2015).…”
Section: Philanthropy; Urban School Board Elections; Intermediary Orgmentioning
confidence: 99%
“…Research on external donor influence on local school board elections is relatively new. In their study of two school board election cycles in four cities, Reckhow et al (2017) found 'that outside donors are competing with unions in local school board elections … some reform groups have portrayed their efforts as intended to counter the traditional insider role of teacher unions ' (796). National organisations, they point out (along with Marsh and Wohlstetter 2013), have an interest in being able to point to successes of various reforms in local settings.…”
Section: Research Contextmentioning
confidence: 99%
“…After Hurricane Katrina devastated the city in 2005, population and political dynamics began to change in New Orleans. As Burns and Thomas (2015, p. 8) note, in post-Katrina New Orleans, “new actors who combined resources and authority displaced the established order in New Orleans.” State officials and national foundations led the efforts to disrupt the existing political arrangements in the city which affected various aspects of local governance including public housing, policing and public safety, and the public school system (Arena 2012; Burns and Thomas 2015; Reckhow et al 2017).…”
Section: Black Political Power and Education Reform In New Orleansmentioning
confidence: 99%